Egyptian uprising : Al-Azhar’s changing position - Afif Pasuni (2012)
The uprising in Egypt and the triumph of its people over the regime has put the role of Al-Azhar, one of the most renowned learning institutions in the Muslim world, into question. As it adjusts itself following Mubarak’s downfall, will it motivate other religious institutions in the region to do the same?